Interventional Pulmonology in 2015: A Survey of Practice Patterns and Future Directions of this Emerging Field - Abid Butt; Rodrigo Cavallazzi; Umair Gauhar (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2016)
Background: Interventional Pulmonology (IP) training through formal fellowship programs have become  increasingly  popular  over  the  last  several years. There  is  a  dearth of  data on  the current practice of IP in the United States. The objective of this study was to identify the practice patterns of current IP practitioners. Methods: We sent a survey to the members of the American Association of Bronchology and In- terventional Pulmonology (AABIP) - the largest association of American IP practitioners. We analyzed the responses and stratified the responses to compare, when possible, how the practice patterns of the IP fellowship trained physicians varied from those who did not undergo formal fellowship training. Results: We received a reply from 97 individuals. There was a noticeable difference in the practice patterns of respondents who had undergone fellowship training in IP versus those who had not, particularly with respect to volume and diversity of procedures performed. A small percentage of respondents appeared responsible for most of the advanced therapeutic procedures as well as on going research in the field of IP. Conclusions: Our study is, to our knowledge, the first to capture the state of affairs of practicing Interventional Pulmonologists in the US. Our survey raises hopes as well as concerns about the benefits associated with an additional year of training in IP. We feel this survey will serve as an important aid for IP practitioners, fellowship directors, and IP fellows (both current and future) to further define clinical and research priorities and to foresee any future challenges in the field.